ENERGY & ENVIRONMENTAL POLICY TRENDS OUR PLANET IN 2040: COMPARING WORLD ENERGY OUTLOOKS - G. Kent Fellows; Victoria Goodday; Rabia Ladha; Jennifer Winter (The School of Public Policy Publications, 2019)
Comparing the predictions of the latest world energy reports gives insights into the world’s progress towards limiting greenhouse gas emissions and meeting the goals of the Paris Agreement. It gives an indication of just how close — or far — we might be from keeping global temperature increases below 2°C by 2100.